MANAJEMEN PENINGKATAN KINERJA GURU SERTIFIKASI SEKOLAH DASAR - Janjuriana, Janjuriana; Marwan, Marwan; Siraj, Siraj (Hijri, 2024)
The purpose of this study is to analyze the management of improving the performance of certified teachers at SD Negeri 2 Syamtalira Bayu, Syamtalira Bayu District, North Aceh Regency. The specific objectives are: 1) analyzing the performance planning of certified teachers, 2) management of certified teacher performance, 3) monitoring and evaluation of certified teacher performance, and 4) problems found in the process of improving the performance of teacher certification This research method is descriptive qualitative research. The sample of this study is teachers and school principals. Data collection techniques are observation, interviews, and documentation. The results of the study explain that the principal's strategy in the planning, monitoring and evaluation stage of improving the performance of certified teachers is going well. The findings of problems in the process of increasing teacher certification are external problems consisting of several factors, including: lack of facilities and infrastructure in the form of inadequate internet networks and insufficient classrooms, lack of support from parents or guardians of students. Internal problems consist of several factors, including: teachers are not optimal in carrying out their duties. Some teachers are less able to develop electronic learning methods and media. The lack of firmness of a leader, in this case the principal, in giving punishment or sanctions to educators who like to violate the rules or disobey the obligations that have been agreed.